A Dual-polarized Reflectarray Antenna for High-speed Ka-band Satellite Communications - Gulseren, Ahmet Hulusi; Yilmaz, Selda; Alparslan, Aytac; Tokan, Nurhan Turker (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2024)
A small-sized reflectarray antenna array with compact production specifications is designed and fabricated for high-speed Ka-band communication systems. In the design phase, firstly, the reflection characteristics of unit cells used in the reflective surface are obtained by the full wave computational analysis tool, CST Microwave Studio. Secondly, an aperture efficiency analysis is carried out to determine the physical size of the reflectarray and the distances between the feeding antenna and the individual unit cells. Then, the entire reflectarray antenna is analyzed by array theory to obtain geometrical dimensions to be used in the fabrication phase. These results are verified by CST Microwave Studio and similar fabrication guidelines are obtained for both TE and TM polarizations. In the fabrication phase, the carefully tailored design parameters of the unit cells are used to build the antenna and measure important parameters such as radiation patterns, gain, cross polarization levels and S 11 parameters, which agree with the results obtained in the design phase. The proposed reflectarray antenna makes it possible to support dual- polarized multi-beams in the range 18-20 GHz with stable gain behavior, which makes it possible to use it in high speed 5G satellite communication systems.
Keywords: Antennas; reflectarrays; satellite communication; DESIGN; Engineering; Telecommunications